An Overview of the Immunization Behavior of the Suku Anak Dalam Community Along the Central Sumatra Line - Ibnu Rahmad, Rizki; Kalsum, Ummi; Halim, Rd.; Nasution, Helmi Suryani; Sitanggang, Hendra Dhermawan (International Journal of Health Engineering and Technology, 2025)
Toddlers have a high level of vulnerability to various diseases. The purpose of this study was to determine the description of immunization behavior and the determinants of immunization behavior of the Suku Anak Dalam community along Lintas Tengah Sumatra. The study used a Cross-Sectional design. Conducted in Bungo Regency and Sarolangun Regency from November 2024 to June 2025. Total sampling technique with a total of 33 mothers of toddlers (0-59 months) in the SAD community. Data were collected through interviews using a questionnaire. Data analysis was descriptive. All mothers of toddlers in the SAD community did not immunize. Some determinants are lack of knowledge (97%), negative attitude (100%), family income <UMK (87.9%), husband does not support (90.9%), access to health facilities is difficult (49.5%), negative customary norms (81.8%) and not exposed to media (42.4%). It is necessary to educate and provide health services that directly reach the SAD community and interpersonal approaches using local languages.